2015
DOI: 10.1016/j.dld.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hepatitis C virus RNA decay, quasispecies evolution and risk of virological failure during telaprevir-based triple therapy in clinical practice

Abstract: The used first generation protease inhibitors may be hampered by virological failure in partially interferon-sensitive patients. Aim: To investigate early hepatitis C virus (HCV)-RNA decay and quasispecies modifications, and disclose viral dynamics underlying failure. Methods: Viraemia decay at early time-points during telaprevir treatment was modelled according to Neumann et al. (1998). NS3-sequences were obtained by population-sequencing and ultradeep-454-pyrosequencing. Results: 13 treatment-experienced (8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…35,37,41–43 Results obtained in studies involving small patient populations found a much slower second phase of viral decline in cirrhotic or treatment experienced patients, than non-cirrhotic treatment naive patients]. 59,60 More data are now needed to precisely evaluate the second phase of viral kinetics with DAAs in “real life” where the proportion of patients with unfavorable characteristics (cirrhosis or treatment experienced) is often larger than in clinical trials. […”
Section: Modelling Ifn-based Therapymentioning
confidence: 99%
“…35,37,41–43 Results obtained in studies involving small patient populations found a much slower second phase of viral decline in cirrhotic or treatment experienced patients, than non-cirrhotic treatment naive patients]. 59,60 More data are now needed to precisely evaluate the second phase of viral kinetics with DAAs in “real life” where the proportion of patients with unfavorable characteristics (cirrhosis or treatment experienced) is often larger than in clinical trials. […”
Section: Modelling Ifn-based Therapymentioning
confidence: 99%
“…As such, treatment-associated variants may have been missed, since it has been reported that NS3 variants tend to disappear within one year after end of therapy (Barnard et al, 2013;Sullivan et al, 2013), and even shorter in the case of newer generation DAAs (Krishnan et al, 2015). For on-treatment sequences, several samples taken at early time points (b14 days) could not be included in the study since it has been shown that RAVs are only detected in plasma after two weeks when using population-based Sanger sequencing (Cento et al, 2015b). A second limitation was the small overall number of NS3 sequences available for the analysis.…”
Section: Selection Of Patients and Sequencesmentioning
confidence: 99%
“…In cases where more than one PI-experienced sequence was available, the latest on-treatment sequence, or if not available, the first post-treatment sequence was selected. Sequences were excluded when the duration of HCV antiviral treatment during which the sample was taken, was b14 days (Cento et al, 2015a(Cento et al, , 2015b. Table 2 summarizes more detailed information for all samples concerning the time of sampling compared to the start and end date of PI treatment.…”
Section: Assignment Of Sequences According To Treatment Groupsmentioning
confidence: 99%
See 1 more Smart Citation